2021
DOI: 10.3390/jcm10143177
|View full text |Cite
|
Sign up to set email alerts
|

Premedication Does Not Influence the Incidence of Infliximab Infusion Reactions in Pediatric Patients with Inflammatory Bowel Disease—A Single Center Case–Control Study

Abstract: Background: Infusion reactions (IRs) are the most common adverse events (AEs) of infliximab (IFX) treatment in patients with inflammatory bowel disease (IBD). Prophylactic premedication (PM) with corticosteroids or antihistamines prior to IFX infusions has been used in clinical practice, but its efficacy is not known. The aim of this study was to assess the influence of steroid PM on IR incidence in pediatric patients with IBD receiving IFX. Methods: We performed a case–control study that included pediatric pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…These findings suggest that biological infusions and IV iron therapies can be administered safely in the same infusion session, potentially leading to significant time savings for patients and limiting the disruptions in work and other activities of daily living. Given that iron replacement has been associated with significant improvements in quality of life among patients with IBD, 15,16 the earlier correction of iron-deficiency anemia in conjunction with biological therapy for disease control may significantly improve clinical outcomes in this population. Among the patients who had an infusion reaction, the administration of premedication with acetaminophen was not significantly different in patient with infusion reactions compared with those without reaction.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that biological infusions and IV iron therapies can be administered safely in the same infusion session, potentially leading to significant time savings for patients and limiting the disruptions in work and other activities of daily living. Given that iron replacement has been associated with significant improvements in quality of life among patients with IBD, 15,16 the earlier correction of iron-deficiency anemia in conjunction with biological therapy for disease control may significantly improve clinical outcomes in this population. Among the patients who had an infusion reaction, the administration of premedication with acetaminophen was not significantly different in patient with infusion reactions compared with those without reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated a reduction in the number of HSR with the use of premedication, especially in cancer patients (39). However, in different clinical setting, the use of premedication is still controversial; despite some initial favorable results (40), most recent data obtained in both adult and pediatric patients suggest that premedication would not change the incidence of infliximab-related HSR (41)(42)(43)(44). To date, there are no definitive data because a specific schedule has never been validated in controlled studies.…”
Section: The Role Of Premedicationmentioning
confidence: 99%